Examining Electrostatic Influences on Base-Flipping: A Comparison of TIP3P and GB Solvent Models (Communications in Computational Physics, 2013)
Recently, it was demonstrated that implicit solvent models were capable ofgenerating stable B-form DNA structures. Specifically, generalized Born (GB) implicitsolvent models have improved regarding the solvation of conformational samplingof DNA [1, 2]. Here, we examine the performance of the GBSW and GBMV modelsin CHARMM for characterizing base flipping free energy profiles of undamaged anddamaged DNA bases. Umbrella sampling of the base flipping process was performedfor the bases cytosine, uracil and xanthine. The umbrella sampling simulations werecarried-out with both explicit (TIP3P) and implicit (GB) solvent in order to establish theimpact of the solvent model on base flipping. Overall, base flipping potential of meanforce (PMF) profiles generated with GB solvent resulted in a greater free energy difference of flipping than profiles generated with TIP3P. One of the significant differencesbetween implicit and explicit solvent models is the approximation of solute-solventinteractions in implicit solvent models. We calculated electrostatic interaction energiesbetween explicit water molecules and the base targeted for flipping. These interactionenergies were calculated over the base flipping reaction coordinate to illustrate the stabilizing effect of the explicit water molecules on the flipped-out state. It is known thatnucleic base pair hydrogen bonds also influenced the free energy of flipping since thesefavorable interactions must be broken in order for a base to flip-out of the helix. TheWatson-Crick base pair hydrogen bond fractions were calculated over the umbrellasampling simulation windows in order to determine the effect of base pair interactionson the base flipping free energy. It is shown that interaction energies between the flipping base and explicit water molecules are responsible for the lower base flipping freeenergy difference in the explicit solvent PMF profiles.